Utilization of Social Media in Agricultural Extension Activities in South Ogan Komering District - Nisma Ulda Sari; Munajat Munajat; Yunita Yunita (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
The development of science and technology today produces many communication media that can be used to share information quickly. There are many alternative communication media available to help disseminate information. The purpose of this study is to determine the factors that influence agricultural extension workers in the use of social media and to determine the use of social media in agricultural extension activities. The research method used survey methods, namely interviews and questionnaires with the first quantitative problem formulation data analysis using simple linear regression and the first qualitative. The results showed that 4 factors influence the extensionist in the use of social media, namely age, internet network, number of social media accounts, and income. Of the four factors, three factors have a significant effect, namely the age factor, internet network, and income, while the factor that has no significant effect is the number of social media accounts. In the second problem formulation of the use of media for agricultural extension activities, there are four social media in the categories used by the extension workers, namely Facebook, YouTube, WhatsApp, and Instagram. Of these media, the most frequently used by extension workers to support extension activities are WhatsApp and youtube. Various kinds of information are accessed on social media, the most sought after by extension workers, namely pest and disease control and information on commodity prices.